PTU-057 Point-Of-Contact Faecal Calprotectin (FC) Testing in Diarrhoea Helps Decision making for Referral to Gastroenterologists: a Primary Care Pilot Study in North East England. (4th June 2013) - Dhar, A; Lee, S H; Borthwick, H; Nair, P; White, C
Abstract : Introduction: Faecal Calprotectin (FC) is a cytosolic protein belonging to the S-100 family of calcium binding proteins found in neutrophils. It is excreted in the intestinal lumen in inflammatory conditions of the gut and can be used to distinguish irritable bowel syndrome (IBS) from other inflammatory bowel conditions such as colitis, diverticulosis, etc. Point-of-contact qualitative FC tests are now available and can be used in primary care to aid decision making for referrals to gastroenterologists for young patients presenting with chronic diarrhoea. Methods Aims: To assess the feasibility and cost effectiveness of a primary care Pathway using a point-of-contact FC Test (Caldetect®) to aid decision making for referrals to gastroenterology in young patients presenting to their primary physicians with chronic diarrhoea. Methods: Primary Care data indicated that approximately 253 referrals are made annually to gastroenterologists from Primary Care to assess patients < 60years presenting with diarrhoea, costing approx. £119, 000 for investigations and consultations. Using a Caldetect® (Preventis, GmbH) point of contact FC test, it was estimated that a saving of £89, 000 could be achieved. A pathway for investigating chronic diarrhoea using Caldetect® was designed and implemented in the community (population 150, 000) between September 2011-March 2012. (this will be presented). FC results were categorised using manufacturer cut-offs of <15 ug/g, 15–60 ug/g and >60 ug/g. Patients with FC results of 15–60 and >60 were deemed to have an inflammatory process and referred to Gastroenterology Clinics. Cost analysis was carried out using the 2010–11 tariffs for the NHS. Results: 142 Caldetect® tests were carried out in Primary Care during this pilot phase. Of these, a negative result (< 15 ug/g) was present in 89, with 36 tests being > 60 ug/g. 3 tests were at the intermediate level and 14 tests could not be accurately reported. Negative results were managed in primary care as IBS. A monthly cost savings of £6100 was calculated taking consultation and endoscopy tariffs into account. Conclusion: This pilot study demonstrates the feasibility and cost effectiveness of a Pathway for decision making and a point-of-care faecal calprotectin test in rationalising referrals to Gastroenterologists for chronic diarrhoea. Disclosure of Interest: A. Dhar Speaker bureau with: Shire Pharamceuticals, Warner Chilcott UK, S. Lee: None Declared, H. Borthwick: None Declared, P. Nair: None Declared, C. White: None Declared